COULD RED CELL DISTRIBUTION WIDTH SERVE AS A NEW INFLAMMATORY MARKER IN CORONARY ARTERY BYPASS GRAFTING? - Murat Günday; Özgür Çiftç; Kazım Körez (Российский кардиологический журнал, 2014)
Aim. In our study, we researched whether on-pump and off-pump coronary artery bypass grafting (CABG) differ as regards their effect on postoperative red cell distribution width (RDW). Moreover, we also investigated whether there was a link between the preoperative and postoperative RDW levels and the early adverse events after CABG.Material and methods. In this study there were 127 consecutive patients who had previously undergone CABG. The patients were divided as group 1 (off-pump, n: 49) and group 2 (on-pump, n: 78). The hemogram and biochemistry panel values were measured a day before the operation, on the first, third and seventh days after it, and in the postoperative first and sixth months.Results. The statistically significant values detected in the hemogram were as follows: postoperative first day hemoglobin, postoperative first day leukocyte, postoperative first day thrombocyte, postoperative first day C-reactive protein, postoperative third day RDW, postoperative third day leukocyte, postoperative seventh day RDW, postoperative seventh day leukocyte, postoperative first month RDW, and postoperative first month thrombocyte (p<0,05). It was found in multivariate analysis that preoperative RDW is an independent risk factor for plasma used in the postoperative period (odds ratio: 0.552; 95% CI: 0.346–0.879; P=0.012). There was no link between preoperative RDW and other early adverse events in the postoperative period (p>0,05).Conclusion. We found that on-pump CABG increases the RDW levels more in the acute period, when compared with off-pump surgery, but that this effect disappears by the sixth month after the operation. For this reason, RDW can be used as a new inflammatory marker in patients undergoing CABG. Moreover, we observed that there was no clinical link between early adverse events after CABG and the pre- and postoperative RDW levels.